Pengaruh Lingkungan Kerja dan Budaya Organisasi Terhadap Motivasi Kerja Pegawai di Bidang Pengelolaan Sampah Dinas Lingkungan Hidup Kabupaten Bandung - Andita Putri Pratiwi; Arie Hendra Saputro (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
Work motivation is a crucial factor in maintaining employee productivity and service quality, particularly in the waste management sector, which requires high levels of physical endurance, discipline, and responsibility. However, in practice, indications of low employee motivation are still observed, which are presumed to be influenced by inadequate work environment conditions and an organizational culture that has not been fully supportive. Such circumstances may affect the effectiveness of task implementation and the overall performance of the institution. This study aims to analyze the effect of the work environment and organizational culture on employee work motivation in the Waste Management Division of the Environmental Agency of Bandung Regency. This research employs a quantitative approach with descriptive and verificative research designs. The population consists of all employees in the Waste Management Division of the Environmental Agency of Bandung Regency, totaling 54 individuals. A saturated sampling technique was applied, in which the entire population was used as the research sample. Primary data were collected through questionnaires developed based on indicators of work environment, organizational culture, and work motivation, using a five-point Likert scale. Data analysis was conducted using SPSS version 26, including validity and reliability tests as well as multiple linear regression analysis. The results indicate that the work environment and organizational culture have a positive and significant effect on employee work motivation, both partially and simultaneously. These findings emphasize the importance of fostering a positive organizational culture and improving work environment conditions to enhance employee motivation and enthusiasm, particularly in the waste management sector.